Cognitive status and low sun exposure as frailty major risk factor among older people in a rural area of East Java, Indonesia: A cross‐sectional study - Soenarti, Sri; Mahendra, Aditya Indra; Rudijanto, Achmad; Soeharto, Setyawati; Ratnawati, Retty; Maryunani; Marintan, Silmy (Geriatrics & gerontology international, 2024)
Aim To reveal the prevalence of frailty and factors that strongly affected the frailty condition among older adults in East Java, Indonesia. Method We conducted a cross‐sectional study carried out among 400 older adults aged ≥60 years without any acute illness. Data were collected from rural area in two locations in Malang and Pasuruan, East Java, Indonesia, in 2019–2020. For data collection, we used the sociodemographic profile assessment, Fried frailty phenotype, Geriatric Depression Scale, Mini Mental State assessment, sun exposure, handgrip strength, International Physical Activity Questionnaire, walk score, and body mass index. We used logistic regression statistics for data analysis. Results The result showed that 2.5% were robust, 83% were prefrail, and 14.5% were frail. A higher proportion of subjects were aged 60–74 years (83.3%), women (70.3%), with lower educational status (84.5%). Multivariate analysis showed that the intrinsic factors low cognitive status (odds ratio [OR], 3.052 [95% confidence interval (CI), 1.691–5.508]) and older age (OR, 3.073 [95% CI, 1.637–5.767]) were associated with frailty among the older adults in a rural area. Depression was also associated with frailty (OR, 2.458 [95% CI, 0.465–12.985]). From extrinsic factors, we also found that low sun exposure (OR, 2.931 [95% CI, 1.650–5.204]) and unemployment (OR, 1.997 [95% CI, 1.112–3.588]) were associated with frailty. Conclusion For the Indonesian elderly in this study, low cognitive status, older age, depression, low sun exposure, and unemployment were associated with frailty. Understanding the modifiable risk factors of frailty can provide a valuable reference for future prevention and intervention. Geriatr Gerontol Int 2024; 24: 170–175. The prevalence of frailty among eldery in rural area of east java Indonesia and its risk factor.